2007
DOI: 10.1016/j.cellbi.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal progenitor cells in adult human dental pulp and their ability to form bone when transplanted into immunocompromised mice

Abstract: The technique of tissue engineering is developing for the restoration of lost tissues. This new technique requires cells that fabricate tissue. Mesenchymal stem cells in bone marrow have been used as the cell source for this technique; however, dental pulp cells have recently been shown to possess stem-cell-like properties. We earlier demonstrated that dental pulp cells proliferate and produce an extracellular matrix that subsequently becomes mineralized in vitro. We now report that such dental pulp cells (fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 29 publications
2
71
0
1
Order By: Relevance
“…On culturing the isolated pulp cells, SHED reached confluency within 14 days, forming an adherent monolayer of visible fibroblast-like colonies in the culture flask, with numerous dividing stem cells [7,23,24]. We used the second passage cultures because as the cultures were passaged, morphological homogeneity was gradually achieved in that flat cells bearing a large nucleoli-rich nucleus predominated, this in accordance with a study by Gronthos et al, 2000 [7].…”
Section: Discussionsupporting
confidence: 64%
“…On culturing the isolated pulp cells, SHED reached confluency within 14 days, forming an adherent monolayer of visible fibroblast-like colonies in the culture flask, with numerous dividing stem cells [7,23,24]. We used the second passage cultures because as the cultures were passaged, morphological homogeneity was gradually achieved in that flat cells bearing a large nucleoli-rich nucleus predominated, this in accordance with a study by Gronthos et al, 2000 [7].…”
Section: Discussionsupporting
confidence: 64%
“…The third molars are the most common source of dental stem cells, because wisdom tooth extraction is widely performed and the teeth are usually considered to be medical waste (Otaki et al, 2007;Yang et al, 2007). Because the third molar is the last tooth to develop in humans, it is normally in an early stage of development and is capable of yielding an optimum quantity of dental pulp tissue for the isolation of DPSCs (Gandia et al, 2008;Laino et al, 2006;Leeb et al, 2010;Morsczeck et al, 2009;Smith et al, 2009;Atari et al, 2011;Zhang et al, 2006a).…”
Section: Discussionmentioning
confidence: 99%
“…Further DePDLSC cell sheets when combined with dentin blocks resulted in the formation of PDL and cementum like tissue on the dentin block however PePDLSCs resulted in formation of no cementum. Numerous other studies carried out in periodontal defect models in animals have reported positive results with application of PDLSC [61][62][63][64].…”
Section: Periodontal Ligament Stem Cell (Pdlsc)mentioning
confidence: 96%